Perancangan Game Edukatif Matematika Menerapkan Pola Labirin Berbasis Mobile - Resi Kiswanto; Atma Hadiansa; Rahmat Hidayatullah (STMIK Budi Darma, 2018)
Mathematics is the study of the magnitude of space structure and change. Mathematics is usually used in the determination of the value of magnitude. Early on, mathematics should be taught to children according to their level. The problem is the lack of interest in the subject of mathematics is often considered difficult. In addition, the tendency of children today who prefer to play games for pleasure alone, so forget the obligation to learn. In solving the problem, there should be an attempt to increase the interest of the child on the subject matter of mathematics. One of them is providing games that are educative, especially that can help understand the math lesson. This study aims to design an educational game of mathematics, which can be useful to increase interest and interest of children to math lessons through the concept of playing while learning more interesting.